Purchasing behavior UiTM students (Sabah branch) on shampoo / Dg Zuraidyah Mohd Yunus - Mohd Yunus, Dg Zuraidyah (2007)
Shampoo is a hair care product used for the removal of oils, dirt, skin particles, environmental pollution and/or other contaminant particles that gradually build up in hair. The goal is to remove the unwanted build-up without stripping out so much as to make hair unmanageable. Shampoo, when lathered with water, is a surfactant, which, while cleaning the hair and scalp, can remove the natural oils (sebum) that lubricate the hair shaft. Shampooing is frequently followed by conditioners, which increase the ease of combing and styling.